Essential components of teacher professional development for financial literacy: A literature review - Louis, Silvya; Siswandari, Siswandari; Noviani, Leny (Intelektual Pustaka Media Utama, 2024)
Financial literacy, as a fundamental skill in the 21st century, has become a life skill that is urgently needed to be improved. Globally, the drive to enhance financial literacy involves integrating it into the education curriculum, necessitating educators’ comprehensive grasp of financial literacy education before imparting it to students. This research aims to outline a conceptual model of financial literacy professional development to improve teachers’ professional competence, employing a narrative review that synthesizes 28 relevant literatures retrieved from Scopus databases. The results of the study show that an effective training model for teacher professional development (TPD) in financial literacy education should focus on essential financial literacy content consisting of planning and budgeting, banking services, income and careers, insurance, investment, savings, also spending and credit. Furthermore, the main characteristics of TPD regarding financial literacy education should encompass content focus, coherence, ownership, active learning, duration, and collective participation.